2021
DOI: 10.1111/iej.13543
|View full text |Cite
|
Sign up to set email alerts
|

European Society of Endodontology position statement: endodontic management of traumatized permanent teeth

Abstract: This position statement represents a consensus of an expert committee convened by the European Society of Endodontology (ESE) on the endodontic management of traumatized permanent teeth. A recent comprehensive review with detailed background information provides the basis for this position statement (Krastl et al. 2021, International Endodontic Journal, https://doi.org/10.1111/iej.13508). The statement is based on current scientific evidence as well as the expertise of the committee. Complementing the recently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 65 publications
0
18
0
3
Order By: Relevance
“…In fact, endodontic treatment might have been initiated in order to enable root canal anchorage for complication-free extrusion. According to current guidelines, (partial) pulpotomy is considered the treatment of choice for fractured teeth with pulp exposure [ 48 , 49 ]. This approach is only feasible when there is sufficient dental hard tissue to bond a bracket and no need for an intracanal anchorage.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, endodontic treatment might have been initiated in order to enable root canal anchorage for complication-free extrusion. According to current guidelines, (partial) pulpotomy is considered the treatment of choice for fractured teeth with pulp exposure [ 48 , 49 ]. This approach is only feasible when there is sufficient dental hard tissue to bond a bracket and no need for an intracanal anchorage.…”
Section: Discussionmentioning
confidence: 99%
“…Most children perceive sensibility pulp testing as unpleasant stimuli, therefore, false-positive and false-negative responses are commonly encountered. Such situations may lead to incorrect treatment strategies [ 28 , 40 ]. Teeth erroneously diagnosed as nonvital may undergo unnecessary endodontic treatments, whereas those erroneously diagnosed as vital may be left untreated, causing further complications to the supporting tissues [ 27 ], and even affecting the successor tooth bud [ 41 ] if primary teeth are involved.…”
Section: Sensibility Pulp Testsmentioning
confidence: 99%
“…Sensibility tests are considered unreliable during the root formation period, due to the underdevelopment of Raschkow’s plexus [ 12 ]. EPT is associated with an increased threshold value in teeth with open apices, which frequently results in increased rates of false-negative results [ 40 ]. HPT have shown limited value because of inconsistent responses, whereas CPT with CO 2 ice proved to offer consistently more reliable results [ 42 ].…”
Section: Sensibility Pulp Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…Guidance published by the European Society of Endodontology (ESE), The International Association of Dental Traumatology (IADT) and the American Academy of Paediatric Dentistry (AAPD) currently indicate that complicated (i.e. exposure of pulp) crown fractures of mature and immature permanent teeth should be treated by a vital pulp therapy, which includes pulp capping or pulpotomy (AAPD, 2014 ; Bourguignon et al, 2020 ; ESE, 2021 ). However, some studies have suggested a higher rate of pulpal necrosis for those teeth treated by pulp capping compared to pulpotomy (Fuks et al, 1982 ; Hecova et al, 2010 ; Wang et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%